Ethnomathematics of Tenun Sipirok in Transformation Geometry: Ethnomathematics of Tenun Sipirok in Transformation Geometry - Sihombing, Amelia Syakinah; Hutagalung, Herdiansyah; Diyah Khoiriyah (RADINKA JAYA UTAMA PUBLISHER, 2024)
Mathematics is often called uninteresting and considered abstract. One way that can be used to introduce mathematics is by relating it to daily life or special local culture, which is called ethnomathematics. Ethnomathematics is a combination of mathematical elements with cultural aspects and social context in society. One of the cultures that exists in society is weaving. In South Tapanuli itself there is a woven cloth which is a local cultural heritage, namely the Sipirok Woven cloth. In this research, the science implemented is Transformation Geometry. Transformation Geometry is a science that discusses change, these changes can be in the form of changes in shape or changes in presentation based on matrices and images. This research is included in the type of exploratory research, namely exploring woven fabric motifs that can be used in learning Transformational Geometry. The process of compiling one element of the sipirok motif can be carried out in various ways and in a certain sequence of transformations. The transformation that will be used to compose sipirok batik in this article is reflection.